2022
DOI: 10.3386/w30381
|View full text |Cite
|
Sign up to set email alerts
|

Scared Straight? Threat and Assimilation of Refugees in Germany

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…We believe we are the first to use a mover-based research design to study the effects of place on migrants' social integration, adding to existing evidence that is observational or relies on quasi-random refugee settlements (e.g. Åslund and Rooth, 2007;Damm, 2014;Braun and Dwenger, 2017;Aksoy, Poutvaara and Schikora, 2020;Jaschke, Sardoschau and Tabellini, 2021;Sale, 2021). We also introduce the use of movers to study the effect of places on native rates of befriending migrants, highlighting that place-based effects are not primarily picking up preferences of local natives.…”
mentioning
confidence: 98%
“…We believe we are the first to use a mover-based research design to study the effects of place on migrants' social integration, adding to existing evidence that is observational or relies on quasi-random refugee settlements (e.g. Åslund and Rooth, 2007;Damm, 2014;Braun and Dwenger, 2017;Aksoy, Poutvaara and Schikora, 2020;Jaschke, Sardoschau and Tabellini, 2021;Sale, 2021). We also introduce the use of movers to study the effect of places on native rates of befriending migrants, highlighting that place-based effects are not primarily picking up preferences of local natives.…”
mentioning
confidence: 98%
“…A second possible choice is to assimilate. Assimilation can take different forms: adopting natives' cultural norms (Jaschke et al, 2022), changing one's name or one's children's names (Fouka, 2019;Saavedra, 2021), marrying a native (Gould and Klor, 2016), or naturalizing (Ferrara and Fishback, 2022;Fouka, 2019). The third option consists basically of keeping one's situation as it is.…”
Section: Thinking About Foreigners' Response To Violencementioning
confidence: 99%
“…Exposure to violence reduces intermarriage rates (Fouka, 2020;Gould and Klor, 2016), knowledge of the host country's language (Steinhardt (2018), though see Chen and Xie (2020)), support for the host country's political system (Fouka, 2020;Grewal and Hamid, 2022). In contrast, others scholars have shown that individuals exposed to violence tend to pick for their newborns names common in the host country (Chen and Xie, 2020;Fouka, 2019;Saavedra, 2021), adopt the cultural practice of their host community (Jaschke et al, 2022), and apply more for naturalization (Fouka, 2019).…”
Section: Thinking About Foreigners' Response To Violencementioning
confidence: 99%
“…They find that positive attitudes towards migrants at the time of arrival, have a positive effect on refugees' economic and social integration. On the other hand, Jaschke et al (2020) rely on the questions on attitudes towards migrants available in the IAB-BAMF-SOEP-Survey of Refugees. They find that more negative attitudes towards migrants lead to a faster cultural convergence of refugees.…”
Section: Literature Reviewmentioning
confidence: 99%